Sampling essentials : practical guidelines for making sampling choices - Daniel, Johnnie (Los Angeles : Sage Publications, 2012)
"Designed for the nontechnical researcher or generalist, this text provides the reader with a good understanding of sampling principles. The author gives a detailed, nontechnical description and guidelines with limited presentation of formulas to help reach basic research decisions, such as when to choose a sample vs. census and nonprobability vs. probability sampling as well as how to select sample size and sample type. Intended for the social and behavioral sciences, Sampling Essentials is appropriate for undergraduate students, graduate students, and research practitioners"--
"Sampling Essentials: A Practical Guide provides comprehensive and detailed guidelines on sampling in social and behavioral research. Broad coverage of key topics, including techniques for conducting online surveys and determining sample size, makes this book an authoritative reference for readers interested in survey methodology or research design. And, the author's non-technical approach is ideal for novice researchers. This book could easily supplement traditional research methods texts, in which sampling is often only covered in one chapter"--
Includes bibliographical references (p. 264-279) and index.
Keywords: Social sciences -- Research; Social sciences -- Methodology; SOCIAL SCIENCE / Research